PRODUKSI KOSAKATA ANAK MELALUI ELECTRONIC WORDLESS PICTURE STORYBOOK - Nurul Arifiyanti; Kartika Ananda (Universitas Negeri Makassar, 2018)
Children’s Vocabulary Production through Electronic Wordless Picture Story-book. This study aims to reveal the effectiveness of the use of electronic wordless picture storybook to improve the production of children's vocabulary. We compared a printed wordless story-book and an electronic wordless storybook. The quasi-experiment research with one group posttest design only was used in this study. The subjects were six teachers and 59 children aged 24-48 months. Samples were taken using a saturated sample technique in three early childhood educational institutions. The instrument used was an observation sheet. The data were then analyzed using the Mann Whitney Test. The result was an electronic wordless picture storybook more ef-effective to produce children's vocabulary.